2013
DOI: 10.1002/2327-6924.12079
|View full text |Cite
|
Sign up to set email alerts
|

Malabsorption anemia and iron supplement induced constipation in post-Roux-en-Y gastric bypass (RYGB) patients

Abstract: Purpose Over 250,000 bariatric surgical procedures for the management of morbid obesity are performed in the United States annually. The Roux‐en‐Y gastric bypass (RYGB) is an effective bariatric procedure because of its efficacy in achieving significant weight loss, low complication rates, and outcomes in reducing cardiovascular and all cause mortality. Because food bypasses the portion of the small intestine whereby micronutrients are normally absorbed, micronutrient deficiencies following surgery may lead to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…However, neither the change in fiber intake, nor the change in water intake, correlated with the change in constipation in the present study. The use of dietary supplements, such as iron, could be another cause of constipation in the post-bariatric patient [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, neither the change in fiber intake, nor the change in water intake, correlated with the change in constipation in the present study. The use of dietary supplements, such as iron, could be another cause of constipation in the post-bariatric patient [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…A major observation in the Brolin study was that 21% of patients in the oral iron group did not take their iron supplement regularly (20). In bariatric surgery patients and in the general population, ferrous sulfate supplementation is known to induce adverse gastrointestinal sideeffects (29,39). These observations suggest that non-compliance is a major issue with oral iron supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…The ineffectiveness of oral iron supplementation for prevention or treatment of iron deficiency may be due to reduced intestinal absorption of iron (25,26) or to low compliance of patients to the regimen (27,28). Users of ferrous sulfate and other formulations of non-heme iron preparations experience gastrointestinal adverse side effects such as diarrhea and constipation because inorganic iron is highly labile (29). However, in a recent cross-sectional study we demonstrated that prophylactic use of oral non-heme iron supplementation was adequate for preserving normal iron status following RYGB (30).…”
Section: Introductionmentioning
confidence: 99%
“…It also may be because patients are not well-informed about the need to continue taking iron supplements for the rest of their lives to maintain adequate iron status. In addition, patients may not be compliant with the regimen because the supplements are costly or not well-tolerated; they are associated with nausea and constipation [17,20,21]. Taken together, the influence of iron ingested from supplements and food sources on iron status in patients who have undergone RYGB is not wellunderstood.…”
mentioning
confidence: 94%